The Dynamics of Voting Behaviour in India: An Analytical Study - shitiri, Shitio; Prof. Moamenla Amer, (IJRDO - Journal of Social Science and Humanities Research, 2025)
Voting is one of the most frequently used terms in the modern age of democratic politics. In democratic systems, voting is a process by which every adult citizen expresses his approval or disapproval of the decisions made by the government, the policies and programmes of different political parties, and the attributes of the candidates who are in the fight to achieve the status of being the representatives of the people. Voting behaviour is one of the most important studies in the field of political science because it provides an insight into the way citizens engage in democracy and use their decisions to influence governance. An empirical study of the factors that determine electoral behaviour reveals that people's choices are usually influenced by numerous non-rational factors. Pressure groups are very persuasive and influence voter behaviour more through emotional and social appeals rather than logic. They often mobilise support using religious and communal identities, money or the charisma of political leaders. Consequently, voter’s decisions are often influenced by social groups and personal feelings rather than analysis of policy and issues. The main purpose of the study is to focus attention on voting behaviour and highlight the determinants of the voting behaviour in India.